Women and self-government in an indigenous territory: Oaxaca, Mexico - Vázquez García, Verónica (2014)
The recognition of Usos y Costumbres as a form of self-government in the municipalities of Oaxaca, Mexico, is an important achievement for native peoples. However, women’s participation inpositions of power remains a challenge. This paper has two objectives: 1) to analyze the factors that contribute to women’s destitution from the mayoralty; 2) to identify the strategies that some of them use to stay in power. Interviews were conducted with all elected female mayors in a ten-year period (1999-2009). Three actors intervene in women’s permanence or destitution: the assembly, the town council and political parties. The second is the most difficult one for women. Some of the strategies used by them to remain in power are: to rely on the assembly as a source of legitimacy; to negotiate government portfolios with council members; to obtain funds and establish links with the state governor.